a Design of a Contactor-Based Automatic Transfer Switch Control System for Two Houses Using a Single Generator as a Backup Power System - Sanda Agung, Rachmad Mohammad (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2025)
The availability of electricity from the State Electricity Company (Perusahaan Listrik Negara, PLN) as the primary power source greatly influences the fulfillment of the community’s electrical energy needs. However, the electricity supply from PLN is not always stable or continuously available. Under certain conditions, power outages may occur due to disturbances in the electrical power system. Therefore, when a power outage occurs, a power supply transfer system from the main source (PLN) to a backup source is required to maintain the continuity of electrical power supply. This system functions as a backup to the PLN power supply and consists of a series of electrical components capable of regulating the power transfer process automatically. This system is known as an Automatic Transfer Switch (ATS), which operates automatically through the control of contactors and timers. This study produced a prototype of an ATS system based on contactor and timer control. The objective of this research is to design and implement an ATS control system using contactors and timers for two houses supplied by a single generator as a backup system. The test results show that the contactor- and timer-based ATS system for two houses with one generator as a backup system operates in accordance with the objectives of the study.